ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK MANDIRI SYARIAH - Wati, Ririn Masitoh; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to see the influence of financial performance which is proxy by buy and sell patterns, profit sharing and rent patterns which are measured by using profitability on banking which are listed in Indonesia Stock Exchange (BEI). As an important institution in the economic matters, a proper performance supervisory by banking regulator is required. The financial statement data has been retrieved from (IDX) which is begun from 1st quarter to 4th quarter in 2010-2014 periods. The sample collection method has been carried out by using purposive sampling method. Profitability is the dependent variable in this research whereas mudharabah, musyarakah, murabahah, istisnha, and ijarah are the independent variables. The statistic methods which have been applied in this research in order to analyze the financial statement to the profitability are data processing and descriptive analysis. The examination of data quality shows that the data is normally realized. The classic assumption test shows the linear correlation among independent variables in the regression model. The examination which has been done by using goodness of fit test shows that mudharabah, musyarakah, muarabahah, istisnha, and ijarah are the explanatory variables of profitability. The result of hypothesis test shows that the variable of mudharabah has significant inflluence to the profitability, meanwhile the variables of musyarakah, muarabahah, istisnha, and ijarah does not have any significant influence to the profitability.Keywords: profit sharing, buy and sell, rent, profitability.